Diseminasi Hasil Studi Kelayakan Kuantitatif dan Kualitatif Obyek Wisata Bendungan Beringin Sila (BBS) Kabupaten Sumbawa - Tajidan, Tajidan; Sukardi, L.; Padusung; Fahrudin (Universitas Mataram, 2025)
The results of quantitative and qualitative feasibility studies of BBS tourism objects need to be disseminated to stakeholders through dissemination activities. The dissemination activity aims to provide understanding and convince stakeholders that BBS is feasible to be developed as a tourist attraction. To achieve this goal, dissemination was carried out which was attended by agencies related to tourism and BBS tourist object managers of Sumbawa Regency. The implementation method uses a mixed method of brainstorming. The results of the dissemination showed that the participants gave a positive response and received support for the realization of BBS as a natural and educational tourist attraction in Utan sub-district, Sumbawa Regency. As a follow-up, preparatory activities have been carried out through cross-sectoral coordination meetings. The coordination meeting was chaired by Assistant-2 for economic affairs of Sumbawa Regency. As a new tourist object, BBS still faces obstacles in its development, including there is no infrastructure and lodging facilities (accommodation) and there is no support for cultural tourism attractions as a driver or attraction for local archipelago, and foreign tourists to come and visit BBS.